Anatomic Basis of Tumor Surgery - Wood, William C.; Staley, Charles A.; Skandalakis, John E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Modern biological understanding is the basis for a multimodality treatment of a tumor. 'Anatomic Basis of Tumor Surgery' is the only book that provides an anatomic basis and description of tumor surgery based on an understanding of both the anatomy and biology of tumor progression. It presents the regional anatomy to allow tailoring of the operation as demanded.
Oral Cavity and Oropharynx -- Neck -- Breast -- Mediastinum, Thymus, Cervical and Thoracic Trachea, and Lung -- Esophagus and Diaphragm -- Stomach and Abdominal Wall -- Small Bowel and Mesentery -- Colon and Appendix -- Rectum -- Pelvis -- Liver, Biliary Tree, and Gallbladder -- Pancreas and Duodenum -- Spleen -- Female Genital System -- Male Genital System -- Retroperitoneum -- Adrenal Glands -- Kidneys, Ureters, and Bladder -- Tumors of the Skin.
Keywords: Medicine; Gynecology; Gastroenterology; Cancer -- Surgery; Surgery; Thoracic surgery; Urology; Medicine & Public Health; General Surgery; Surgical Oncology; Gynecology; Urology/Andrology.; Thoracic Surgery; Gastroenterology